Probing InGaN immiscibility at AlGaN/InGaN heterointerface on silicon (111) through two-step capacitance-voltage and conductance-voltage profiles. (5th November 2017) - Bag, Ankush; Majumdar, Shubhankar; Das, Subhashis; Biswas, Dhrubes
Abstract: Immiscibility of InGaN hinders epitaxial growth of high-quality AlGaN/InGaN heterojunction, which could have superior performances than AlGaN/GaN in view of high-speed devices. AlGaN/InGaN/GaN double heterostructures have been grown on silicon (111) substrate using plasma assisted molecular beam epitaxy. All growth conditions for each sample have been kept identical except the InGaN channel thickness. Alloy inhomogeneity has been found to occur in the InGaN channel by high resolution (HR) X-ray diffractometer (XRD) and cross-sectional HR- transmission electron microscopy (TEM). This non-uniformity of alloy causes reduced indium incorporation with a decrease of channel thickness along with a thin InN binary alloy. Capacitance-voltage (C-V) profile has revealed non-uniformity of alloy and spatial position of InN in the channel due to variation of band-offset and carrier confinement. Unconventional two-step profile has been obtained for the heterostructure. Higher capacitance at near zero bias corroborates the formation of InN at AlGaN/InGaN due to larger band offset. Conductance-voltage (G-V) profiles further validate mapping of InGaN phase separation in terms of carrier trapping. Lower effect of trapping has been identified due to low bandgap InN formation at the interface. Effect of epilayer relaxation on the phase separation has also been discussed in terms of threading dislocation and V-defects. Graphical abstract: Highlights: AlGaN/InGaN heterostructure has been grown on GaN/Si(111) using plasma assisted molecular beam epitaxy. Non-conventional two-step profile has been observed using capacitance-voltage and conductance-voltage techniques. Impact of strain on phase separation of InGaN channel has been found in presence of V-defects and threading dislocations. Grading of indium incorporation has occurred in InGaN channel along with InN alloy at the AlGaN/InGaN. The heterojunction implicates to act as a pool of static charges for designing new devices.